GAIN ENHANCEMENT TECHNIQUE OF WLAN SINGLE ELEMENT CYLINDRICAL DIELECTRIC RESONATOR ANTENNA (CDRA) BY USING REFLECTORS - ALI, SYED MUZAMMIL (2015)
Adesign of cylindrical dielectric resonator antenna (CDRA) with three different types of reflectors is introduced for wireless local area network WLAN IEEE 802.11a application. The design utilized aperture coupling technique and reflectors to achieve high gain for the antenna. The types of reflector explored are; flat, box shaped and parabolic reflector. The reflectors are implemented at the back of the CDRA design to reflect the backward radiation and consequently improving the forward gain of the antenna. The effect of reflectors on the resonant frequency, impedance bandwidth, directivity gain and backlobe level of CDRA are analyzed by using CST 3D Microwave Studio software. An equivalent circuit model for single element CDRA is proposed to validate the structure with lumped elements values. Additionally, a criterion that determines the dependence of the lumped elements such as capacitance, inductance and resistance on the tuning parameters of the circular slot is demonstrated.